Pelaksanaan Tanggung Jawab Hukum Anggota Koperasi atas Pengalihan Objek Jaminan Sepeda Motor Tanpa Persetujuan Kreditur dalam Kondisi Wanprestasi: Studi Empiris pada Koperasi Simpan Pinjam Langgeng Mulyo Ngancar Kediri - Endro Puji Astoko; Zainal Arifin; Ali Huristak Hartawan Hasibuan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The transfer of motorcycle loan collateral without the approval of cooperative management is a common issue in the financing practices of savings and loan cooperatives. This study aims to analyze the practice of transferring collateral by cooperative members who are in default without the consent of the cooperative management, as well as to examine the legal consequences and forms of legal protection provided by the cooperative. This research employs an empirical legal research method with a socio-juridical approach. Data were collected through interviews, observations, and document studies at Koperasi Simpan Pinjam Langgeng Mulyo Ngancar Kediri, supported by primary and secondary legal materials. The results indicate that the transfer of collateral without the approval of the cooperative management constitutes a breach of contract and may be classified as both default and an unlawful act. Such actions reduce the cooperative's control over the collateral object and increase the risk of losses related to loan assets. The legal protection implemented by the cooperative remains predominantly repressive and has not been optimal from a preventive perspective. Therefore, it is necessary to strengthen loan agreement clauses, enhance supervision of collateral objects, and provide legal education to cooperative members in order to minimize similar violations in the future.